PERLINDUNGAN HUKUM YANG DIBERIKAN TERHADAP PEMEGANG SAHAM DALAM UNDANG-UNDANG NOMOR 40 TAHUN 2007. - SULISTYAWATI, NI PUTU YUNIKA (Kerta Dyatmika, 2015)
ABSTRACTÂ Forms of Legal protection granded to minority shareholders in the Act number 40 of 2007 is given right for the minority shareholders to protect its importance: each shareholders have right to propose claim to the company to district court if aggrieved as resulted by company action that assumed un-fair as resulted of decision of (shareholders general meeting) RUPS, management or commisioner on behalf of company, shareholders which represented at least 1/10 of total share with valid voting right able to propose claim to board of management or comissioner that caused by their fault make loss for the company each shareholders have right propose to the company in order their stock should buy with fair price.Â Keywords: Legal Protection, Minority Shareholders, Act Number 40 of 2004.Â